Considerations about Profilicollis altmani (Perry, 1942) Van Cleave, 1947 in Peru - Tantaleán-V., Manuel (2004)
An analysis of the type, paratypes, cystacanths and intermediate host of Polymorphus bullocki Mateo, Córdova and Guzmán, 1982 make evident that is conspecific with Profilicollis altmani (Perry, 1942) Van Cleave, 1947.